Employee informal participation in occupational safety and health management in a pharmaceutical organisation in Ghana - Baku, Anita Asiwome Adzo (2018)
The reported increasing rate of workplace accidents, injuries, and deaths across the globe in the literature indicates a persistent problem of workplace safety. In most jurisdictions, laws have been used to curb accident rates. In other jurisdictions like Ghana, existing laws are not comprehensive and do not require employee participation like other countries. Management research suggests that employee participation in management results in positive organisational outcomes. Whilst research abounds on representative participation and formal participation, minimal research exists on informal participation. Therefore, this study was conducted to bridge this literature gap. Using the social exchange theory as the overarching theory, the study discovered that informal participation could provide effective alternatives for the management of occupational safety and health. A qualitative research approach using a single case study strategy was adopted. Data was collected from a Ghanaian pharmaceutical manufacturing organisation through individual and group interviews, observations, and document analysis. A total of 60 persons in the organisation were either interviewed or engaged in focus group discussions. Significant among the contributions of this study are the development of a conceptual framework, the identification of factors which encourage and hinder employee informal participation, and the establishment of a link between employee informal participation and improved safety behaviour. The study recommends that future studies should use the quantitative approach to test the validity of the relationships identified in the conceptual framework developed in this study.